The Effect of Teacher Competence on Student Learning Outcomes - Marioga Pardede; Selamat Karo-Karo; Yona Gulo; Fransiskus Gultom (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of teacher competence on the learning outcomes of grade IX students at SMP Negeri 1 Pulau Rakyat Asahan. The population in this study were all components in the school environment, such as: principals, teachers, administration, and students of SMP Negeri 1 Pulau Rakyat Asahan, namely 185 people. The sample in this study were class teachers and grade IX students totaling 50 people. This type of research is quantitative research with the approach used is correlational. The sampling method is purposive sample, namely a sample determination technique with special considerations so that it is worthy of being used as a sample. The data collection method used by the researcher is observation, questionnaire distribution, and documentation. The collected data were analyzed using statistical analysis techniques, namely the product moment correlation test. The results of hypothesis testing using correlation analysis show that the calculated r value is 0.6514 at a significance level of 5% and the r table is 0.279, meaning that the calculated r value is greater than the r table value, namely 0.6514 > 0.279. Thus, the working hypothesis (Ha) is accepted and the working hypothesis (H0) is rejected, meaning that it can be stated that there is an influence of teacher competence on student learning outcomes at SMP Negeri 1 Pulau Rakyat Asahan. The implication of this study is as a reference material to improve teacher competence, especially for science teachers at SMP Negeri 1 Pulau Rakyat Asahan.